Implementation of preeclampsia screening and prevention during pregnancy: a scoping review - Lilik Hanifah; Yu Ying Lu; Anggie Pradana Putri; Catur Setyorini; Anita Dewi Lieskusumastuti (Universitas Aisyiyah Yogyakarta, 2026)
Preeclampsia remains a leading cause of maternal and fetal morbidity and mortality worldwide. Despite its significant impact, early detection and prevention remain suboptimal. Therefore, identifying effective screening approaches and key preventive interventions is essential to optimize maternal and neonatal outcomes. This scoping review aims to evaluate the implementation of preeclampsia screening and prevention during pregnancy. This literature study used a scoping review method, and the literature search used three databases: PubMed, ScienceDirect, and JSTOR. Study selection was performed in accordance with predefined inclusion and exclusion criteria using the PRISMA-ScR flow diagram. The Mixed Methods Appraisal Tool (MMAT) was used to conduct the critical appraisal. Of the 2,819 articles reviewed, twelve studies met the predefined eligibility criteria and were included in the review. These articles came from various countries and consisted of randomized controlled/clinical trials, prospective observational studies, cross-sectional studies, and qualitative studies. Three themes emerged: preeclampsia screening, preeclampsia prevention, and influencing factors. In conclusion, screening and prevention of preeclampsia require collaboration among healthcare providers. Practical strategies include routine blood pressure and proteinuria screening, early risk identification, patient education, and timely referral for high-risk cases. Integrating these interventions into antenatal care can improve early detection thereby contributing to improved maternal and fetal survival by reducing preventable deaths.